Human perception towards the association between the domestic rock pigeon and the insect vector of Chagas disease in an urban area of Argentina - Fernández-Maldonado, Viviana Noemí; Borghi, Carlos E. (Ethnobiology and Conservation, 2022)
This article focuses on identifying risk factors through the knowledge, perceptions, and prevention practices of the population regarding the rock pigeon and the vector of Chagas disease (vinchucas) in an urban area of Argentina. The study used interviews of focal groups, family nuclei with nearby nesting sites and without nearby nesting sites. Among the results, some risk factors that contribute to the infestation of vinchucas in houses were identified, such as presence of nesting sites of the rock pigeon, and frequency of cleaning the nests and of fumigation. We show that people that kept their houses clean of nests and routinely disinfected their homes had considerably lower probability of finding vinchucas within their houses. We also identify a general lack of knowledge about risk factors of Chagas disease related to the presence of nesting sites in houses, the form of dispersion of the vector and how to act upon encountering a vinchuca. However, respondents who presented nests in their houses associated the encounter of vinchucas with the presence of nesting sites. The respondents showed high levels of support for programs to control the population of the rock pigeon. It is important that the population at risk of contracting Chagas disease can combat this disease through their daily actions. Promoting better knowledge of risk factors would be an important advancement for community compliance and participation in the fight against Chagas disease.